Audiological Profile of Patients with Vitiligo - Fayaz, Inna; Saraf, Neha; Kalsotra, Gopika; Kalsotra, Parmod; Mahajan, Vikas; Dilawar, Samreen; Kalsotra, Sahil (International Archives of Otorhinolaryngology, 2025)
Vitiligo is one of the most common causes of hypopigmentation; it occurs when melanin production is impaired due to the loss of melanocytes, which are present throughout the skin, in the epidermis, and in hair follicles, and are also seen in the mucosa, uvea, and several structures of the inner ear. Scientists have investigated the association between vitiligo and sensorineural hearing loss (SNHL); some believe there is a connection, while others disagree.To evaluate the relationship between vitiligo and SNHL.The present observational study was conducted from February 2023 to January 2024. A total of 54 patients with clinically diagnosed vitiligo were assessed for hearing impairment. Simultaneously, 50 healthy volunteers were included as a control group, and the data was analyzed to assess any potential association between vitiligo and SNHL.The mean age of the control group was of 37.5(± 10) years, and that of the patients with vitiligo was of 38.8(± 11) years, and the male-to-female ratio was of 1:1. We observed SNHL in 32 (59.3%) patients with vitiligo, and those with vitiligo vulgaris were the most afflicted. The hearing loss was mild in 2 ears (3.1%), moderate in 24 (37.5%), and severe in 29 (45.3%), with 29 patients belonging to the group with high frequency hearing loss.Based on the findings; it is imperative that patients with vitiligo undergo routine auditory function assessments to facilitate the early detection of SNHL.
Keywords: vitiligo; SNHL; audiometry; ABR